THE EFFECTIVENESS OF MAKE A MATCH IN COOPERATIVE LEARNING HOTS ORIENTED TO THE MATHEMATICS LEARNING OUTCOMES OF STUDENT CLASS XI - Yolan Nur Vitasari; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Teacher-dominated learning causes student mathematics learning outcomes below. This study aims to determine the presence or absence of differences and compare the effectiveness of conventional learning models with cooperative learning models of making a match on students' mathematics learning outcomes of the 11th Textile class of SMK Negeri 2 Sewon, Bantul Regency, 2017/2018 Academic Year. This research is quantitative, with a population of 11th-grade students consisting of 68 students. The samples were randomly selected and class XI Textile 3 as the experimental class and XI Textile 2 as the control class. Data collection techniques used to test techniques. Test of research instrument used validity test, reliability test, and different power test. Analysis prerequisite tests include normality and homogeneity tests. Data analysis used two-party and one-party tests. The results showed differences in mathematics learning outcomes that used conventional learning models with a cooperative learning model type to make a match. The value of indicates this and which means Â and the cooperative learning model type make a match is more effective than conventional learning models on mathematics learning outcomes. This is indicated by and which means .